Analysis Planting Character Belief Self Child Age 4-5 Years through Storytelling Method - Rahmawati, Lia; Nasution, Fauziah (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
Low student curiosity, lack of communication between teacher and students during the teaching and learning process, and some children who still cannot speak fluently have low student self-confidence. The purpose of this study was to give children the confidence they need to introduce their favorite animals to their teachers and friends and to discuss their favorite animals in front of their friends and teachers. The subjects of this study were 20 students from Bakti Pertiwi PAUD, Batang Pane II Village, East Halongonan District, Kab. North Padang Lawas, observations were made while collecting data through interviews with the school and teachers. Miles and Huberman's model is used in data analysis techniques, and there are four stages in the data analysis process: data reduction, data presentation, drawing conclusions, and verification with triangulation. According to the research findings, some children started speaking more confidently after Bakti Pertiwi PAUD started using storytelling techniques because children started to feel more comfortable sharing stories about their favorite animals.